MAKNA SOSIAL BUDAYA DALAM CITY BRANDING TERNATE KOTA REMPAH - Alhaddad, Yahya (CV Kalimasada Group, 2025)
City branding is not only a communication strategy that plays a crucial role in building a positive image but also in strengthening a city's identity. This study aims to identify, analyze, and examine the socio-cultural meanings of the city branding